2023
DOI: 10.1101/2023.01.24.525109
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatially Resolved Transcriptomic Analysis of the Germinating Barley Grain

Abstract: Seeds, which provide a major source of calories for humans, are a unique stage of a flowering plant's lifecycle. During seed germination the embryo reactivates rapidly and goes through major developmental transitions to become a seedling. This requires extensive and complex spatiotemporal coordination of cell and tissue activity. Existing gene expression profiling methods, such as laser capture microdissection followed by RNA-seq and single-cell RNA-seq, suffer from either low throughput or the loss of spatial… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…A deeper investigation of the shared markers of germinating seeds revealed that many of the identified genes with shared expression across cell types encode a diverse range of ribosomal protein subunits. The unified expression of ribosomal proteins across cell types in the germinating seed dataset coincides with global increases in ribosome biogenesis and translation during seed germination in both Arabidopsis 41,42 and Barley grains 43 . While the expression of many ribosomal protein genes is present across several cell types of germinating seeds, this was not observed for all of the other tissues assayed, where subsets of ribosomal proteins were expressed only in specific cell types among all tissue and organs assayed, supporting the hypothesis that the heterogeneous composition of ribosomes is developmentally regulated 44 , and may explain the higher levels of homogeneity within this tissue.…”
Section: Resultsmentioning
confidence: 82%
“…A deeper investigation of the shared markers of germinating seeds revealed that many of the identified genes with shared expression across cell types encode a diverse range of ribosomal protein subunits. The unified expression of ribosomal proteins across cell types in the germinating seed dataset coincides with global increases in ribosome biogenesis and translation during seed germination in both Arabidopsis 41,42 and Barley grains 43 . While the expression of many ribosomal protein genes is present across several cell types of germinating seeds, this was not observed for all of the other tissues assayed, where subsets of ribosomal proteins were expressed only in specific cell types among all tissue and organs assayed, supporting the hypothesis that the heterogeneous composition of ribosomes is developmentally regulated 44 , and may explain the higher levels of homogeneity within this tissue.…”
Section: Resultsmentioning
confidence: 82%
“…This allows for the examination of how a gene's expression level changes temporally along a continuous process [7][8][9][10][11][12][13] . ST, on the other hand, measures both the gene expression and spatial locations of single cells or small clusters of cells, enabling the direct interrogation of spatial gene expression patterns from the observed data [14][15][16][17][18][19] .…”
Section: Mainmentioning
confidence: 99%
“…In orchids, the crucial roles of MADS-box genes and other potential downstream genes in organ initiation and morphogenesis have been elucidated through spatial transcriptomics (Liu et al, 2022a). By combine the temporal and spatial expression distribution of genes during maize kernels development constructed a comprehensive gene network regulating in grain filling process (Fu et al, 2023), By adding different germination time to barley germination spatial transcriptomics also help to reveal aquaporin gene families and auxin transport genes roles in zygote embryo activation and embryo polarity establishment processes (Peirats-Llobet et al, 2023). Meanwhile, integrating single-nucleus and spatial transcriptomics could enhance resolution of plant-microbe interactions in nodulating plants (Liu et al, 2023b).…”
Section: Introductionmentioning
confidence: 99%